(untitled) (Homoeopathy for All, 2024)
Homoeopathy is curative system of medical branch. In Homoeopathy patient is treated as a whole. Each patient having their own peculiar individual symptoms. In Homoeopathy physical as well as mental symptoms are consider completely. This article is an attempt emphasizing Homoeopathic approach migraine. This article also help in increasing the knowledge on therapeutic properties of the highly recommended remedies and useful rubrics to select most similimum. And in Homoeopathy migraine is easily cured if the medicine symptoms and patient symptoms are same. If the remedy is selected properly than it can give spectacular results. Homoeopathy remedies are given by watching susceptibility of the person.